The Influence of Social Media on Millennial Generation about Travel Decision-Making - Nur'afifah, Oktavia; Prihantoro, Edy (Universitas Semarang, 2021)
The presence of the millennial generation in the world of tourism has different characteristics from the previous generation. They are not interested in commercial advertising but prefer a User-Generated Content (UGC) approach and influence in their social environment. The purpose of this research is to determine the influence of social and UGC on Instagram on millennial generation travel decision-making. Instagram was chosen because 67% of travelers use Instagram for travel inspiration before booking a trip and after a trip is booked, and continue to use it for future trips. The sample of this study was 384 millennial respondents in the Greater Jakarta area because it had the demographic bonus and the most productive age. The results show that UGC on Instagram is highly trusted as a media for millennial tourism decision-making because it is authentic and reliable. This research also succeeded in answering the phenomenon which states that the millennial generation can change the tourism industry. This finding is useful for destination managers and the government in their efforts to increase the promotion of tourist destinations to the millennial generation with the Instagram user-generated content approach.